Antenatal Screening for the Frequency of Subclinic Hypothroidism - Erdal Ödöl; Miğraci Tosun; Burcu Torumtay; Tayfun Alper; Erdal Malatyalıoğlu; Mehmet Çetinkaya; Arif Kökçü (Medical Network, 2009)
OBJECTIVE: The objective of this study is to investigate the frequency of subclinical hypothyroidism in pregnant population. STUDY DESIGN: This study was performed in Ondokuz Mayıs University Obstetrics and Gynecology Clinic between January 2006 - September 2006. Six hundred forty nine pregnant women between 17 - 46 ages were included into the study. The pregnant women who have evident or subclinical hypothyroidism in their medical history were excluded from the study. The study was done by searching TSH, fT3, fT4 levels by using Electrochemiluminescence immunoassay (ECLİA) analisators. All pregnant women were evaluated according to age, height, weight, body mass index (BMI). Mann Whitney U and Chi-square test were used for statistical assessment. RESULTS: Subclinical hypothyroidism was detected in 4 % of 649 screened women. When demographic and physical parameters taken into consideration, there were no statistically significant differences between women having hypothyroidism and normal hormone levels. CONCLUSION: Subclinical hypothyroidism which was detected in % 4 of pregnant women in Samsun and places near it.